Simulation Research on Train Derailment and Collision Accident in Urban Rail Transit - WEI Liang; LIAN haishan; YI Fuqing (Chengshi guidao jiaotong yanjiu, 2024)
Objective The process of a stainless steel train body derailment accident in urban rail transit in 2015 is simulated, reproducing the direct cause and process of the car body damage in the complex accident scene. Method Based on the investigation of the accident scene and the stainless steel car body structure and characteristics, the finite element method is used to reconstruct the accident model and analyze the changes of the speed, acceleration and energy of the train. Result & Conclusion Simulation results show that the intermediate cars climbing, snaking and colliding with each other caused by huge energy and rugged ground at the time of the accident forms the main reason for the fracture failure of stainless steel car body structure in the accident. The car body fractures mainly locate at the connections between the cab frame and the under-frame, the end wall and the roof, the under-frame and the side wall, as well as the under-frame and the end wall.